Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/1612-2011/13/12/126201
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switched thulium-doped fiber laser with silver-nanoparticle film as the saturable absorber for operation at 2.0µm

Abstract: In this work, a compact thulium-doped fiber laser with a Q-switched output is proposed and demonstrated. A thulium-doped fiber is used for the laser, with a peak absorption of 200 dB m−1 at 790 nm and a cutoff wavelength of 1350 nm as the primary gain medium, and a silver-based saturable absorber as the pulse generation mechanism. The pulses obtained from the proposed laser have repetition rates from 38.3 kHz up to 56.2 kHz, with a pulse width as low as 4.2 µs and pulse energy as high as 67.3 nJ at a maximum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In 2016, Ahmad first utilized SNPs SA to achieve a Q-switched TDFL operating at 2 µm, which exhibited application prospects in eye-safe applications. [157] Notably, Lv et al reported on modelocked lasers at 1, 1.5, and 2 µm realized by the silver nanowire (SNW) SA with a minimum pulse duration of 464 fs and SNR up to 63 dB. Figure 11a shows the scanning electronic microscopy (SEM) image of the prepared SNWs.…”
Section: Silver-based Sas At 2 and 3 μMmentioning
confidence: 99%
“…In 2016, Ahmad first utilized SNPs SA to achieve a Q-switched TDFL operating at 2 µm, which exhibited application prospects in eye-safe applications. [157] Notably, Lv et al reported on modelocked lasers at 1, 1.5, and 2 µm realized by the silver nanowire (SNW) SA with a minimum pulse duration of 464 fs and SNR up to 63 dB. Figure 11a shows the scanning electronic microscopy (SEM) image of the prepared SNWs.…”
Section: Silver-based Sas At 2 and 3 μMmentioning
confidence: 99%
“…[82] In 2016, Ahmad et al firstly reported on a SNPs-based SA for TDFL at 2 μm, in which a highly stable Q-switched pulse with SNR of 59.5 dB was achieved, suggesting the potential for eye-safe applications such as manufacturing and medicine. [195] In 2019, Li et al proposed an ion implantation method for embedding the SNPs in neodymium-doped YAG crystal to design a monolithic device, in which a Q-switched mode-locked (QM) pulse with a maximum repetition rate of 10.53 GHz was firstly achieved in 1064-nm monolithic waveguide laser. [98] In addition, Rosdin et al obtained a stable mode-locked pulse by using a SNPs-PVA SA in EDFL, the corresponding SNR of 74.3 dB indicated the stable mode-locking of the pulse.…”
Section: Goldmentioning
confidence: 99%
“…In 2018, Duan et al realized a 734 ns Q-switched Ho,Pr:LLF laser at 3 μm by using gold nanoparticles (Au-NPs) as a SA [11]. In addition, a 2 μm Q-switched laser based on Ag-NPs SA has also been developed [12]. Nevertheless, the disadvantage of the high cost of these noble metals has limited the incentive for further research.…”
Section: Introductionmentioning
confidence: 99%